Charged-cellulose nanofibrils as a nutrient carrier in biodegradable polymers for enhanced efficiency fertilizers. (15th November 2022) - França, Débora; Siqueira, Gilberto; Nyström, Gustav; Clemens, Frank; Souza, Claudinei Fonseca; Faez, Roselena
Abstract: An enhanced efficiency fertilizer (EEF) is essential for sustainable agriculture, and here, we evaluated cellulose nanofibrils (CNF) as a nutrient carrier dispersed in biodegradable polymeric matrices. CNF were functionalized with negative (CNF − ) and positive (CNF + ) charges to improve (i) the CNF-nutrient and (ii) the CNF-polymeric matrix interactions. The CNF encapsulated the KNO3 nutrient by spray drying (microcapsules) and then inserted into a poly (hydroxybutyrate)/starch-based matrix by melt-compounding (tablets). These materials were morphologically, structurally, and thermally characterized before and after biodegradation. Nutrient release profiles showed the microcapsules released the nutrients for up to 1 h, while the tablets did for 8 h in water and over 80 days in soil. Tablets with CNF − released NO3 − faster than K +, and those with CNF + behaved inversely. Besides, the biodegradation efficiencies were up to 75 % in 120 days. The CNF charges affected nutrient release and the matrix biodegradation, ensuring the matrices were harmless to the environment. Graphical abstract: Unlabelled Image Highlights: Biodegradable matrices for EEF based on PHB, starch, and CNFs. Functionalized-CNF improved the microencapsulation of the nutrient. Functionalized-CNF improved microcapsules-polymer matrix interactions. CNF into the matrices increased the biodegradation levels. Different CNF charges release the K + and NO3 − differently.